ANALISIS NILAI TAMBAH (VALUE ADDED) AGROINDUSTRI PEMINDANGAN IKAN DI KELURAHAN BINTARO KECAMATAN AMPENAN KOTA MATARAM - MARINI, IDA AYU KETUT; ARTIKA, IDA BAGUS EKA (GANEC SWARA, 2024)
Fresh fish has a perishable nature (Perishable food) requires a processing process so that it has a longer shelf life, is easier to distribute, and is easier to consume. Marinating is a processing and preservation technique by boiling or cooking fish in salted conditions for a period of time. certain conditions in a container and then the process of reducing the water content to a certain limit occurs. This research is entitled "Analysis of Value Added (Value Added) Fish Farming Agroindustry in Bintaro Village, Ampenan District, Mataram City which aims to determine the added value produced from fresh tuna after processing into pindang fish. The type of research used was descriptive research with the research location in Bintaro Village, Ampenan District, Mataram City. Added Value Analysis used the Hayami table method (1987). Based on the results of calculations, one production process required an average of 816 fresh tuna fish. kg and produced 489 kg of pindang fish. The average price of pindang fish per kilogram is IDR 37,500, so the average level of income for the pindang fish business is IDR 11,010,000 per production process. Then the added value generated in this research is IDR. 2,113,988, with a value added ratio of 19.2%.